2010
DOI: 10.1007/s00423-009-0585-6
|View full text |Cite
|
Sign up to set email alerts
|

Does internal stenting of the pancreaticojejunostomy improve outcomes after pancreatoduodenectomy? A prospective study

Abstract: Internal stenting of a duct-to-mucosa pancreatojejunostomy does not diminish the rate of pancreatic fistula formation or alter overall patient's outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…On the other hand, most studies and meta-analyses report no statistically significant difference in POPF incidence with internal stent use. [26][27][28][29] Nevertheless, internal stenting appears to have been successful in avoiding complications since none of the True-DMA patients developed postoperative pancreatitis, pancreatic insufficiency, or duct stricture as shown by follow up CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most studies and meta-analyses report no statistically significant difference in POPF incidence with internal stent use. [26][27][28][29] Nevertheless, internal stenting appears to have been successful in avoiding complications since none of the True-DMA patients developed postoperative pancreatitis, pancreatic insufficiency, or duct stricture as shown by follow up CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a debate regarding pancreatic duct stenting and its drainage methods. Although some authors have reported similar complication rates between stented and non-stented patients,2526 we believe that it is necessary to stent the anastomosis to promote duct-mucosa healing, especially in patients with a small pancreatic duct 27. With respect to the stent drainage methods, external drainage showed somewhat better results in terms of morbidity 28.…”
Section: Discussionmentioning
confidence: 83%
“…Subsequent screening resulted in four prospective randomized trials examining only external pancreatic stents following PD [6][7]9,14]. Of note, the present study excluded two trials previously included by Markar et al [10]; 1) the 2009 prospective trial conducted by Smyrniotis et al [5] on the basis that this study examined internal stents only, and 2) the 2006 trial conducted by Winter et al [4] on the basis that internal stents were included and because these authors utilized an alternating method of allocating patients to either treatment or control arms, which may have inadvertently introduced selection bias as described by Doll [15]. Baseline and intra-operative demographics of the study populations are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This is then closed with a purse-string suture, externalized via a stab incision in the anterior abdominal wall, and closed by suturing the serosa of the jejunum to the peritoneum of the abdominal wall. In both cases migration of the catheter is prevented with an absorbable suture attachment to the jejunal mucosal surface [4][5][6][7][8][9]. The final PJ reconstruction is then carried out with an end-to-side, duct-to-mucosa anastomosis using 1-or 2-layer interrupted fine sutures [6].…”
mentioning
confidence: 99%